2001
DOI: 10.1248/bpb.24.236
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nonpeptidic Inhibitors of Herpes Simplex Virus Type 1 and Human Cytomegalovirus Proteases.

Abstract: Herpes simplex virus type 1 (HSV-1) and human cytomegalovirus (HCMV) belong to the family Herpesviridae and cause severe opportunistic infections in immunocompromised individuals, including organ transplant recipients and AIDS patients. [1][2][3] Present clinical therapies commonly use viral DNA polymerase inhibitors such as acyclovir and ganciclovir, but this approach has been accompanied by the emergence of resistant mutants and various toxicities. 1)Therefore, treatment clinics need new antiviral drugs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Несмотря на сходство структур, 1,4-дигидроксинафталин ингибирует протеазу ВПГ-1 по конкурентному механизму, тогда как 3 нафтохинона являются неконкурентными ингибиторами. Действие этих соединений селективно в отношении герпетических протеаз, они не проявляют существенной ингибирующей активности против сериновых протеаз млекопитающих (химотрипсин, трипсин, калликреин, плазмин, тромбин и фактор Xa) в концентрации 100 мкМ [43]. Таким образом, вышеописанные непептидные соединения могут представлять интерес для дальнейшего изучения их активности in vivo.…”
Section: ингибиторы герпетической протеазыunclassified
“…Несмотря на сходство структур, 1,4-дигидроксинафталин ингибирует протеазу ВПГ-1 по конкурентному механизму, тогда как 3 нафтохинона являются неконкурентными ингибиторами. Действие этих соединений селективно в отношении герпетических протеаз, они не проявляют существенной ингибирующей активности против сериновых протеаз млекопитающих (химотрипсин, трипсин, калликреин, плазмин, тромбин и фактор Xa) в концентрации 100 мкМ [43]. Таким образом, вышеописанные непептидные соединения могут представлять интерес для дальнейшего изучения их активности in vivo.…”
Section: ингибиторы герпетической протеазыunclassified
“…Through screening of a compound library, Matsumoto et al (2001) discovered 4 compounds, 1,4-dihydroxynaphthalene and 3 naphthoquinones, which effectively inhibit HSV-1 protease. Further study indicated that these compounds were potent and selective inhibitors of CMV protease, with extremely low IC 50 values.…”
Section: Herpes Virusesmentioning
confidence: 99%